PENGATUH ROA TERHADAP PENGUNGKAPAN CSR - Venesia Abigael Nagara; Hisar Pangaribuan (Jurnal Ekonomis, 2021)
This study aims to determine the Effect of Return On Assets (ROA) on CSR Disclosure. In this study, 106 samples were used (composed of 53 Indonesian, Malaysian, and Singaporean banking companies from 2018 to 2019). The method used in this study is purposive sampling, where the criteria for the companies being observed are companies that are observed are banking companies in each country. The results of the research that have been carried out show that based on the t test, it shows that ROA has no significant effect on CSR. This statement is based on the evidence found that the significant value of ROA is 0.279 > 0.05. This result explains that the size of ROA has no effect on CSR. Therefore, the first hypothesis which reads "Significant Effect" on the ROA variable on CSR disclosure is not proven.